Refusal strategy used by Malay and German native speakers to refuse requests - Mohd Jalis, Farhana Muslim; Abdul Jabar, Mohd Azidan; Abdul Halim, Hazlina; Burkhardt, Jurgen Martin (Canadian Center of Science and Education, 2019)
This study investigates similarities and differences in Malay and German refusal speech acts realised by their respective mother tongue languages, which are the Malay and German languages. This study analysed situations in which refusal could occur and examined the refusal strategies and corresponding linguistic forms used by the two groups when refusing requests made by higher, equal, and lower relationship status interlocutors. A Discourse Completion Test (DCT) was utilised to obtain data on the types and content of refusal strategies. The data gathered from the DCT was analysed and coded according to a combined taxonomy of refusal strategies proposed by Beebe et al. (1990) and Al-Issa (2003). The findings will provide future insights on the cross-cultural complexity of refusal interaction patterns used by both Malay and German speakers in order to understand and also avoid creating stereotypes of foreign culture. In addition, speakers may also adopt socially appropriate strategies for future situations that might be encountered in order to engender successful communication when dealing with refusals. The results are then discussed from the universality and cultural-specificity perspectives.